'Digital sonosphere'. Diagnosis of its current analytical applications and terminological meanings. Issue 1 (2nd January 2020) - Torras i Segura, Daniel
ABSTRACT: Recently, in the academic and artistic field, the term ' digital sonosphere' —or sometimes simply ' sonosphere' —has started to be widely disseminated and used. Confronting this relatively new term from a scientific perspective has generated a lot of pertinent doubts related to its connotations, functional ambit, definition and the reality it describes. Through a review of the scientific literature, this research proposes a revision and evaluation of the term ' digital sonosphere' . This work aims to identify the functional application of the concept studied, its added value compared to existing concepts and, at the same time, to highlight its deficiencies related to scientific use in the study of sound perception nowadays. The conclusions of this research present the term 'digital sonosphere' as ambiguous, context-dependent and redundant in relation to existing terms. Nevertheless, the term's application is considered useful in some specific types of analysis.